2019
DOI: 10.1002/pbc.27657
|View full text |Cite
|
Sign up to set email alerts
|

Results of a multicenter universal newborn screening program for sickle cell disease in Italy: A call to action

Abstract: Background Sickle cell disease (SCD) is a chronic multisystem disorder requiring comprehensive care that includes newborn screening (NBS) as the first step of care. Italy still lacks a national SCD NBS program and policy on blood disorders. Pilot single‐center screening programs and a regional targeted screening have been implemented so far, but more evidence is needed in order to impact health policies. Population and methods NBS was offered to parents of newborns in gynecology clinics in Padova and Monza, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The prevalence of SCD in developed countries is increasing partly due to migration from high prevalent countries [17][18][19][20]. It is estimated that over 14,000 people live with SCD in the UK, similar to France, while countries like Italy, Germany have seen increasing numbers from Africa [21][22][23][24]. With increasing survival, the age distribution of SCD is changing from a childhood disorder pattern that patients now survive into adulthood and old age.…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of SCD in developed countries is increasing partly due to migration from high prevalent countries [17][18][19][20]. It is estimated that over 14,000 people live with SCD in the UK, similar to France, while countries like Italy, Germany have seen increasing numbers from Africa [21][22][23][24]. With increasing survival, the age distribution of SCD is changing from a childhood disorder pattern that patients now survive into adulthood and old age.…”
Section: Epidemiologymentioning
confidence: 99%
“…Established diagnostic test procedures for SCD are currently available: The results of test-positive newborns screened using tandem mass spectrometry or HPLC, for example, showed that they were actually affected by SCD, since no false-positive results were reported in selected studies (e.g. [ 29 , 30 ]). Since the factors influencing test accuracy may vary, essential factors for the widespread use of such screening programmes are the training of laboratory personnel, laboratory standards, and the minimum amount of blood per sample to be analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria selective environment in these regions further augmented the gene frequencies. Recent migrations have also contributed to the prevalence of the gene in regions with low or no malaria prevalence, for instance in southern Africa ( 16 ), North America ( 3 ) and Europe ( 17 ).…”
Section: Common Variants In Haemoglobin Genesmentioning
confidence: 99%